Pengembangan E-Modul Tipe Flipbook Berbasis Studi Kasus Stunting untuk Meningkatkan Penguasaan Konsep pada Materi Sistem Pencernaan - Windy Oktaviani; Margaretha Solang; Masra Latjompoh (Postgraduate, University of Mataram, 2023)
The study aims to describe the validity, practicality and determine the effectiveness of flipbook-type e-modules based on stunting case studies to improve the concept mastery on digestive system material. This research uses research and development methods modified. Data collection techniques using observation sheets, questionnaires and tests. The trial was conducted on 37 students of Class XI IPA 2 SMA Negeri 1 Kabila. The research results found: (1) validity tests is in â€œVery Goodâ€ category based on the percentage of content/material validation of 87.50% and construction validation of 98.00% (2) practicality test is in